Analisis pengaruh rasio keuangan terhadap Return On Asset (Roa) pada Perusahaan Perbankan Tahun 2017- 2021 - Septiyani , Eka; Maryono, Maryono; Santosa , Agus Budi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this thesis is to analyze and test the effect of financial ratios on return on assets (ROA). This study has. Variables such as carrent adequacy ratio (CAR), non performing loan (NPL), net interest margin (NIM), operating costs to operating. Income and loan to deposit ratio (LDR). The research method used in this research is descriptive qualitative research analysis method. This study selects the banking industry on the variables studied. Retrieval of annual financial report data from the ojk web and the bei web. According to the selected sample criteria, 43 companies went public. Multiple linear regression test was used to analyze the data and the method to process the data was Microsoft Excel and SPSS 22. The results of this study shows the results of the variables car, and bopo variables have a negative significant effect on roa. Npl has no significant negative effect on ROA, and the variable nim has a positive and significant effect on ROA as will as. The ldr variable has no effect on ROA